2019
DOI: 10.1038/s41467-018-08110-z
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of in vivo dynein force production by CDK5 and 14-3-3ε and KIAA0528

Abstract: Single-molecule cytoplasmic dynein function is well understood, but there are major gaps in mechanistic understanding of cellular dynein regulation. We reported a mode of dynein regulation, force adaptation, where lipid droplets adapt to opposition to motion by increasing the duration and magnitude of force production, and found LIS1 and NudEL to be essential. Adaptation reflects increasing NudEL-LIS1 utilization; here, we hypothesize that such increasing utilization reflects CDK5-mediated NudEL phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Importantly, we find that KASH5 recruits LIS1 as well as dynein and dynactin, and that LIS1 is needed for dynactin recruitment to KASH5. LIS1 is crucial for dynein function where high force is needed (Chapman et al, 2019; Markus et al, 2020; Pandey and Smith, 2011; Reddy et al, 2016; Yi et al, 2011), and has recently been shown to increase force generation of dynein-dynactin complexes in vitro by promoting the recruitment of two dynein motors per dynactin (Elshenawy et al, 2020; Htet et al, 2020; Markus et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we find that KASH5 recruits LIS1 as well as dynein and dynactin, and that LIS1 is needed for dynactin recruitment to KASH5. LIS1 is crucial for dynein function where high force is needed (Chapman et al, 2019; Markus et al, 2020; Pandey and Smith, 2011; Reddy et al, 2016; Yi et al, 2011), and has recently been shown to increase force generation of dynein-dynactin complexes in vitro by promoting the recruitment of two dynein motors per dynactin (Elshenawy et al, 2020; Htet et al, 2020; Markus et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, multiple Dynein adaptors such as Ndel1L, Lis1 or BICD, have been reported to be phosphorylated by either kinases 47,48,32 and could be the link to Bin1. Additional layers of regulation are certainly at play as both Cdk5 and GSK3β regulate Dynein processivity, in addition to cargo loading 32,33,49,50 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the physiological and functional relevance of reduced dynein protein expression coupled with sustained retrograde transport remains to be studied further. It has been shown that CDK5 regulates dynein force adaptation for mitochondria and lysosomes (Chapman et al, 2019) by stabilizing the dynein-NudEL-LIS1 complex to enhance dynein force production. Since CDK5 is also activated in AD (Liu et al, 2016) and phosphorylates tau (Kimura et al, 2014), it is likely that decreased dynein in P301L cells might be an early adaptation mechanism to fine-tune the transport from being too robust in the retrograde direction.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the molecular mechanisms underlying reduced mitochondrial transport, we have generated a heterologous tauopathy model by overexpressing P301L in COS7 cells. COS cells provide an excellent model for understanding signaling aspects of tau-mediated transport, as tau is not present in COS cells (Chapman et al, 2019), ruling out the possible confounding effects of tau on microtubules. Cells expressing P301L show increased phosphorylation compared to either wild-type or GFP expressing cells (Figures 3A,C).…”
Section: Overexpression Of P301l Impairs Parkin Translocation To Mito...mentioning
confidence: 99%